Controlled release of silver nanoparticles from monolayers deposited on PAH covered mica - Oćwieja, Magdalena (Langmuir : the ACS journal of surfaces and colloids, 2013)
Systematic studies of silver particle deposition kinetics under diffusion transport on poly(allylamine hydrochloride) (PAH) modified mica were carried out. Monolayer coverage, quantitatively determined by AFM and SEM, was regulated within broad limits by adjusting the deposition time and the ionic strength. The stability of obtained silver films was determined in controlled release experiments also carried out under diffusion transport for pronged time periods reaching 240 h. The decrease in the surface coverage of particles was followed by SEM and AFM imaging. The role of particle size, ionic strength, and temperature was systematically studied. It was determined that particle release kinetics was enhanced by increase in ionic strength and temperature, whereas the effect of particle size was less significant. These results were theoretically interpreted in terms of the random sequential adsorption model (RSA), which allowed one to determine the equilibrium adsorption constant Ka and the binding energy (energy minimum depth). For particles of the average size 15 nm and T = 298 K, the energy varied between -16.9 kT for ionic strength 0.1 M and -18.8 kT for ionic strength 10(-4) M. For the largest nanoparticles 54 nm, the energy varied between -17.7 kT for ionic strength 0.1 M and -20.8 kT for ionic strength 10(-4) M. These results suggest that the interactions between surface and nanoparticles are mainly controlled by electrostatic attraction between ion pairs. Our studies indicate that there is a possibility of a controlled release of silver nanoparticles from films formed at solid substrates, which can be significant for biological application, e.g., in respect to antibacterial activity